LEXICON FORM OF LANGUAGE VARIATION ON SHOPEE LIVE (ETHNOLINGUISTIC STUDIES) - Islakhiyah, Islakhiyah (Department of English Literature, Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
The intense communication and interaction of the Shopee Live feature’s user creates a distinctive language variation that is often used by the prolocutor and the interlocutor to increase the existence, efficiency and familiarity between users. Departing from this, this research which will focus on the form and meaning of lexicons in the language variation used by prolocutor and interlocutors of Shopee Application is an ethnolinguistic study with a structural approach to explain how language variation become media and provide precise definition of the prolocutor and the interlocutor characteristics. The objective of this research is to classify the form and meaning of lexicons in the language variation used on the Shopee Live Streaming feature. This research is a type of qualitative descriptive research. Data was collected using participant observation and documentation techniques from the primary and secondary data source. The research data is in the form of a lexicon that is often used by users of the Shopee Live feature, which is collected from primary data and secondary data. The researcher found 84 numbers of data that will be examined. The researcher concludes that the evolvement of shopping language from traditional to online shopping system is due to the shifting of cultural behaviour owned by the prolocutor and the interlocutor.